Compensation of damages to victim of criminal offence under Criminal Procedure Code of Ukraine - Мудрак, Інна Василівна; Мудрак, І. В.; Мудрак, Инна Васильевна; Mudrak, Inna V.; Подобний, Олександр Олександрович; Подобний, О. О.; Подобный, Александр Александрович; Podobnyi, Oleksandr O.; Ващук, Олеся Петрівна; Ващук, О. П.; Ващук, Олеся Петровна; Vashchuk, Olesia P. (Society of Juridical and Administrative Sciences, 2019)
A significant number of criminal offenses affects the life, health or property of citizens, accompanied by physical, property or moral harm. It must be admitted that the most important right of a victim in a criminal procedure is the right to compensation for damages caused by criminal offenses. Today, in Ukraine, the legal regulation of the victims’ right to compensation is not in line with constitutional guarantees, therefore measures from the state to strengthen these guarantees are relevant. In this view, international instruments that regulate the compensation for victim in the criminal procedure are analyzed, as well as the practice of developed countries. The evolution of the Ukrainian legislation concerning compensation to the victim in the criminal process is described.The difference in the terminology of international acts, acts of developed states and Ukrainian legislation in relation to compensation to victim is revealed. It is concluded that it is worthwhile to use the term “compensation”. It is noted that Ukraine needs to take into account the experience of foreign countries in compensating for the harm caused to victim in a criminal procedure at the expense of the State budget. This mechanism can be implemented by creating a State Victim Assistance Fund that would function as a specific credit institution.

Значна кількість кримінальних правопорушень завдає шкоди життю, здоров’ю чи майну громадян, що супроводжується фізичною, майновою чи моральною шкодою. Слід визнати, що найважливішим правом потерпілого в кримінальному процесі є право на відшкодування збитків, завданих кримінальними правопорушеннями. Сьогодні в Україні правове регулювання права потерпілих на компенсацію не відповідає конституційним гарантіям, тому заходи держави щодо посилення цих гарантій є актуальними. З цієї точки зору аналізуються міжнародні документи, що регулюють компенсацію потерпілому в кримінальному процесі, а також практика розвинених країн. Описано еволюцію законодавства України щодо відшкодування шкоди потерпілому в кримінальному процесі. Виявлено відмінність у термінології міжнародних актів, актів розвинених держав та законодавства України щодо компенсації потерпілому. Зроблено висновок, що доцільно використовувати термін «компенсація». Зазначається, що Україні необхідно враховувати досвід іноземних держав щодо відшкодування шкоди, заподіяної потерпілому у кримінальному процесі за рахунок державного бюджету. Цей механізм може бути реалізований шляхом створення Державного фонду допомоги потерпілим, який функціонуватиме як окрема кредитна установа.
Mudrak I. Compensation of damages to victim of criminal offence under Criminal Procedure Code of Ukraine / I. Mudrak, O. Podobnyi, O. Vashchuk // Juridical Tribune. - Vol. 9. - № 2. - Society of Juridical and Administrative Sciences, 2019. – Р. 377-391.
Keywords: criminal procedure of Ukraine; victim; compensation of damages; property damages; moral damages; harm; criminal offence; repair of damages; кримінальний процес України; потерпілий; відшкодування збитків; майнові збитки; моральна шкода; шкода; кримінальне правопорушення; відшкодування збитків; Research Subject Categories::LAW/JURISPRUDENCE